Gas Bubbles Expansion and Physical Dependences in Aluminum Electrolysis Cell: From Micro- to Macroscales Using Lattice Boltzmann Method. (23rd February 2014) - Diop, Mouhamadou; Gagnon, Frédérick; Min, Li; Fafard, Mario
Abstract : This paper illustrates the results obtained from two-dimensional numerical simulations of multiple gas bubbles growing under buoyancy and electromagnetic forces in a quiescent incompressible fluid. A lattice Boltzmann method for two-phase immiscible fluids with large density difference is proposed. The difficulty in the treatment of large density difference is resolved by using nine-velocity particles. The method can be applied to simulate fluid with the density ratio up to 1000. To show the efficiency of the method, we apply the method to the simulation of bubbles formation, growth, coalescence, and flows. The effects of the density ratio and the initial bubbles configuration on the flow field induced by growing bubbles and on the evolution of bubbles shape during their coalescence are investigated. The interdependencies between gas bubbles and gas rate dissolved in fluid are also simulated.